2023
DOI: 10.1149/1945-7111/ad0919
|View full text |Cite
|
Sign up to set email alerts
|

From Atoms to Wheels: The Role of Multi-Scale Modeling in the Future of Transportation Electrification

Taylor R. Garrick,
Yangbing Zeng,
Jason B. Siegel
et al.

Abstract: Traditionally, prototype hardware is built for validation testing to ensure battery systems design changes meet vehicle-level requirements, which is expensive both in cost and time. Virtual engineering (VE) of battery systems for electric vehicle (EV) propulsion offers a reduced-cost alternative to the traditional development process and uses multi-scale modeling to virtually probe the impact of design changes in a particular part on the overall performance of the system. This allows for rapid iteration over m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 37 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…Automotive engineers must rely on virtual engineering methods that can accurately capture the performance of battery cells that allows for the linkage of cell design to the system level and vehicle level performance and requirements. 72 Having a closed form algebraic solution to the MSMR model linked to the entropy coefficient allows for reduced order models to be generated and removes the need for a lookup table, enabling real-time, 73,74 efficient solving of models for rapid virtual analysis of battery cell performance, and linkage to the reversible heat generation in thermal models for lithium ion batteries.…”
Section: Resultsmentioning
confidence: 99%
“…Automotive engineers must rely on virtual engineering methods that can accurately capture the performance of battery cells that allows for the linkage of cell design to the system level and vehicle level performance and requirements. 72 Having a closed form algebraic solution to the MSMR model linked to the entropy coefficient allows for reduced order models to be generated and removes the need for a lookup table, enabling real-time, 73,74 efficient solving of models for rapid virtual analysis of battery cell performance, and linkage to the reversible heat generation in thermal models for lithium ion batteries.…”
Section: Resultsmentioning
confidence: 99%
“…Prior to manufacturing the battery cell, battery models can be utilized to drive design by linking the performance requirements of a battery cell in a particular system to the electrode and material level design choices during the development phase. 1 After a battery has been implemented into the target system, battery models are developed to predict the physical state of a battery and track degradation dynamics to optimize performance, efficiency, and long-term health. 2 Battery Management Systems (BMS) sustain safe battery operating conditions, manage thermal loads, and perform fault detection during operation to detect scenarios that lead to undesired events.…”
mentioning
confidence: 99%
“…The large format battery cells used in this study were from the GMC Hummer EV Pickup electric vehicle as reported in our previous work. [46][47][48] The cells used here have a capacity of 101.8 Ah at a C/3 discharge rate. The cell is built with a stacking construction with alternating cathodes and anodes with separators placed in between.…”
Section: Methodsmentioning
confidence: 99%
“…Silicon and other high-capacity anode materials undergo significant volume change [19][20][21][22][23] during lithiation, [24][25][26] which can ultimately impact the performance of the battery pack and electric vehicle due to the engineering changes that must be made to account for the silicon volume change. Additionally, a desire exists to increase the speed 27 at which battery cell designs move from concept to production reality. To that end, using virtual methods to drive cell and system level changes for electric vehicles and grid storage becomes critical, and in turn, quantifying the impact of lithiation induced volume changes in any battery cell active material is necessary to drive the virtualization of the design and prototyping phase for electric vehicle development.…”
Section: Background and Introductionmentioning
confidence: 99%